Protocols for Stakeholder Participation in Social Marketing Systems. (September 2018) - McHugh, Patricia; Domegan, Christine; Duane, Sinead
Stakeholder participation is the systematic mapping of potentially influential actors who can affect or be affected by intervention(s). Literature to date acknowledges the presence and interrelatedness of multiple stakeholders but is extremely limited in its approach on how to systematically identify and encourage stakeholder participation in social marketing systems. To address this limitation, this article responds to Buyucek et al.'s call for "stakeholders to be systematically identified and managed throughout the intervention design, planning and implementation." This research proposes stakeholder participation as important to social marketing, regardless of whether it is for a single intervention or systems. We describe and demonstrate seven protocols for stakeholder participation in social marketing systems. We apply an illustrative participatory research context that follows the seven protocols of stakeholder participation and their related sets of tasks, tools, and activities and designed to identify, classify, and map stakeholders across marine environmental social marketing domains. The participatory research context illustrates that working "with" stakeholders rather than "on" their behalf can build bridges and transform societies. We then discuss the implications of embedding a stakeholder participation orientation in social marketing systems—for example, the complexities associated with multilevel stakeholder identification, partnership formation, ownership, conflict and continuity, and the value derived from interlocking co-creation and participatory processes for change.